2018
DOI: 10.1128/jvi.00900-18
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antibody Interactions with the G Protein of Vesicular Stomatitis Virus Indiana Strain and Other Vesiculovirus G Proteins

Abstract: VSVind.G is currently regarded as the gold-standard envelope glycoprotein to pseudotype lentiviral vectors. However, recently other G proteins derived from vesiculoviruses have been proposed as alternative envelopes. Here, we investigated two commercially available anti-VSVind.G monoclonal antibodies for their ability to cross-react with other vesiculovirus G proteins, identified the epitopes they recognize, and explored their neutralization activity. We have identified 8G5F11, for the first time, as a cross-n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Sera were isolated and pooled, and neutralizing activity was determined through an in vitro LV neutralization assay previously described (Figure 1). 20 VSVind.G-LV infection was blocked in a dose-dependent manner; however, a similar effect was also observed for LVs pseudotyped with the unrelated feline endogenous retrovirus RD114-derived (RDpro) envelope (Figure 1A, dotted lines). This unspecific neutralizing activity suggested that the inhibition of LV infection might be due to antibodies directed against proteins on the vector surface acquired from the producer cells during the LV production, namely, host-cell proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sera were isolated and pooled, and neutralizing activity was determined through an in vitro LV neutralization assay previously described (Figure 1). 20 VSVind.G-LV infection was blocked in a dose-dependent manner; however, a similar effect was also observed for LVs pseudotyped with the unrelated feline endogenous retrovirus RD114-derived (RDpro) envelope (Figure 1A, dotted lines). This unspecific neutralizing activity suggested that the inhibition of LV infection might be due to antibodies directed against proteins on the vector surface acquired from the producer cells during the LV production, namely, host-cell proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Here we demonstrate that while close phylogenetic relatives of VSVind.G, MARAV.G and COCV.G, share its receptor usage, the more distant PIRYV.G does not. The phylogenetic closeness of PIRYV.G and Chandipura G 20 implies that vesiculoviruses might be split into at least two groups regarding their primary receptor for cell entry.
Figure 5PIRYV.G Does Not Interact with sLDLR(A) VesG- and RDpro-expressing HEK293T cells were incubated with (left) VSV-Poly and anti-RD114 antiserum to determine envelope expression and (right) sLDLR in parallel. The cells were then probed with the respective secondary antibodies to determine envelope expression and anti-6XHis-tag antibody for sLDLR binding.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…H and F envelope proteins from the measles virus (MV) have been used to retarget various cell types. More recently other proteins have been considered as alternative envelopes for LV pseudotyping such as glycoproteins derived from other vesiculovirus subfamilies, Cocal, Piry and Chandipura viruses or the VSV New Jersey strain as well as the Nipah virus and other rhabdoviruses, for which it was proposed that they could have an advantage over the commonly used VSV-G Indiana strain [37,38]. However, it is difficult to obtain high-titer vectors with some of these glycoproteins, though they transduce efficiently hematopoietic cells (Summary in Table 1).…”
Section: Pseudotypingmentioning
confidence: 99%